Quality of accounting information disclosure on technological R&D: comparative analysis of reports filed in Brazil and the United States by Brazilian companies - Canongia, Marco Aurélio Goulart; Silva, Adolfo Henrique Coutinho e (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: To analyze and compare the accounting information disclosure level on technological Research & Development (R&D) expenditures in accounting reports filed in Brazil and the United States by publicly traded Brazilian companies from different industrial sectors and listed as American Depositary Receipts (ADR) on the New York Stock Exchange. Methodology: Qualitative comparative analisys, based on a multiple case study, with an emphasis on documentary analysis of the 2022 accounting reports filed with the Brazilian Securities Commission (CVM) and the U. S. Securities and Exchange (SEC). Results: The evidence shows that there are differences in quality, such as organization, clarity and detailing, in the disclosure of initiatives and expenditures in technological R&D activities presented by the companies studied. In the Form 20-F reports, filed with the SEC, the information is more detailed and organized than the information disclosed in the Standardized Financial Statements (DFP), filed with the CVM, characterizing dependence on the target market and non-compliance with CVM guidelines. The deficiencies identified in the disclosure of information on R&D expenditures highlight the existence of opportunities to reduce information asymmetry between reports. Contributions of the Study: The study contributes by highlighting the importance of the actions of capital market regulators in complying with current regulations, improving monitoring mechanisms and improving the quality level of information disclosure on R&D expenses in Brazil.